2019
DOI: 10.1159/000496548
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index at Diagnosis as a Prognostic Factor for Early-Stage Invasive Breast Cancer after Surgical Resection

Abstract: Background: The aim of this study was to investigate the association between body mass index (BMI) and prognosis of Chinese women with breast cancer. Patients and Methods: 3,380 primary breast cancer patients who underwent surgery from 2010 to 2012 were selected and classified as low BMI group (BMI < 25.0) and high BMI group (BMI ≥ 25.0). The follow-up data for disease-free survival (DFS) and overall survival (OS) were obtained from 3,178 patients (median follow-up of 58 months). Cox regression analysis was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…The starting point was the date of operation, and all ended on December 30, 2019. As we reported previously 33 . For patients who died, the date and cause of death were recorded, and all deaths not attributable to breast cancer were censored at the date of death.…”
Section: Methodssupporting
confidence: 72%
“…The starting point was the date of operation, and all ended on December 30, 2019. As we reported previously 33 . For patients who died, the date and cause of death were recorded, and all deaths not attributable to breast cancer were censored at the date of death.…”
Section: Methodssupporting
confidence: 72%
“…Yet, independently to menopausal status, obese women achieve poorer clinical outcomes [ 92 ]. Wang et al showed that females above 50 years old with greater Body Mass Index (BMI) are at a greater risk of cancer compared to those with low BMI [ 93 ]. Besides, the researchers observed that greater BMI is associated with more aggressive biological features of tumor including a higher percentage of lymph node metastasis and greater size.…”
Section: Risk Factors Of Breast Cancermentioning
confidence: 99%
“…Epidemiologically, estrogen receptor-positive breast cancer develops in obese women in the postmenopausal period ( Kolb and Zhang, 2020 ). However, women more than 50 years of age with greater BMI are at higher risk of breast cancer than those with low BMI ( Wang et al, 2019 ). However, it has been reported that people with a higher BMI are at a high risk of tumors with a high percentage and size of lymph node metastasis.…”
Section: Modifiable Risk Factorsmentioning
confidence: 99%